Innovative Approaches in Architecture and Planning the Future of Our Past - Boudiaf, Bouzid (ICONARCH International Congress of Architecture and Planning, 2014)
Historic Arab cities show a variety of origins and modernization patterns; these were conditioned on the one hand by external factors such as pre-existing settlements, deliberate locational choices and prevailing dynastic modernization and transformation, on the other hand by internal factors such as the morphological principles implied in individual architecture components and in genesis of the urban environment. In this paper, we will try to highlight the socio-cultural aspects in the city structure context and their relations to the city morphology referring to the underlying shaping forces of urban form which, drawing on related, deep-rooted human attitudes, constitute the real agents of physical manifestation and are source of the non-material qualities transpiring through materials expressions. This presentation seeks to understand the significance of the city structure in different dimensions of urban environment. Understanding the interaction between underlying political, economic, socio-cultural forces as deep structure elements is an important aspect of research objectives. This paper also studies how physical or functional changes follow changes in the underlying forces among the modernization process and city structure regeneration. The approach to the research objectives is based on two methodologies: Deductive: a theoretical investigation based on the properties of the city structure, definitions, principles of design, and the dilemma of achieving modernization is as much cultural as technical. This combines information from literature reviews and the ideas of key figures in the urban development field and the place-identity, social identity and identity process as theories for cultural models of the city. Inductive: a study of Algiers as example of historical settlements that have undergone much change processes. The study looks to elicit the images of the city main structure to support the theoretical propositions of surface and deep structural city elements. The conclusion to this part is based on an analysis of the case study. The research concludes its conclusion through the theoretical and empirical work the socio- cultural aspect in the modernization process as a board and complex field. Moreover, it introduces the concept of City Structure as a new way to envisage urban Conservation studies.